The influence of maternal behavior in infant and young child feeding with stunting - Yusnaini Yusnaini; Kartinazahri Kartinazahri; Iin Fitraniar; Cut Yuniwati; Ampera Miko (AcTion: Aceh Nutrition Journal, 2024)
Stunting in children under the age of five is the result of a prolonged lack of nutritional intake or past malnutrition, such as feeding that does not meet nutritional needs. Maternal behavior during feeding is an important factor to consider. This study aimed to determine the effect of maternal behavior on the incidence of stunting in children aged 3-4 years. The research used a case-control design in the coastal area of the Aceh Jaya Health Center in May 2024. The sample was children aged 3-4 years as many as 69 children, divided into two groups, namely cases of stunted children and controls were normal children. Data were collected through interviews, using questionnaires, and anthropometric measurements of height and age. Data analysis was performed using the chi-squared test. Results: There was an influence between maternal behavior in feeding and the incidence of stunting in children (p = 0,039; OR = 2,9); thus, mothers with poor behavior had an increased risk of stunting in children by 2,9 times. In conclusion, maternal feeding behavior influences the incidence of stunting in children aged 3-4 years in the coastal area of the Aceh Jaya Health Center.